Pengaruh pengetua, guru, ibu bapa, rakan sebaya dan penggunaan internet dalam membentuk kefahaman dan amalan sahsiah pelajar / Yakcop Jantan - Yakcop, Jantan (2017)
The aimed of this research work is to identify the principals’ leadership roles, teachers, parents, peers, and internet influences in developing students’ understanding and practice of good personality among form four students of Kuala Lumpur. This work is also designed to investigate teachers’ mediating roles in developing students’ understanding and practice of good personality. This study also aimed to identify the proposed statistical model of the research variables in developing students’ personality fit to the research population. A total of 297 form four students were randomly selected from six schools of Kuala Lumpur. Pilot test on 32 students showed that Cronbach’s Alpha internal validity was between .72 and .94 for all the research variables. The results showed that the overall level of students’ understanding and practice of good personality was moderately high. On the inferential part, Structural Equation Modelling (SEM) using AMOS was conducted to test the predictive power of the research variables showed a moderately strong relationship of students’ understanding and practice of good personality. The analysis revealed that there were a direct significant impact on teachers, parents, and peers in developing students’ understanding and practice of good personality at p < .05. But, parental control on their children showed a low level of relationship in developing students’ understanding and practice of good personality. However, there is no significant direct impact of two other variables i.e. the principals’ leadership roles and internet influences at level p < .05 in developing students’ personality.Further analysis were conducted and the results revealed that there were a small direct impact and moderately indirect impact of principals’ leadership roles in developing students’ understanding and practice of good personality. However, indirectly (through teachers mediated role), the principal played a significant higher role in enhancing students’ understanding and practice of good personality. It showed that the cooperation between the principals and their teachers is an important factor in developing students’ understanding and practice of good personality. Implication of the study has therefore explicated that the higher the teachers play a role, the higher the level of students’ understand of good personality; the higher the teachers play a role and students’ understand of good personality, the higher the level of students’ practice of good personality among form four students of Kuala Lumpur. Therefore, authorities who are responsible in developing a personality curriculum, needs to formulate programmes that aim at enhancing teachers’ competencies development as part of the effort to improve students’ understanding and practices of good personality. In the same vein, the higher the level of parental control of their children, the higher the students understand of good personality; and the higher the level of the parents control of their children, the higher the students understand of good personality, the higher the children practice of good personality. Therefore, parents need to put an additional effort in shaping the fabrics of their children as a way of helping them to uncover good personality.